Detection of Uropathogens by Using Chromogenic Media (Hicrome UTI agar), CLED agar and other Conventional Media - Parveen, R; Saha, SK; Shamshuzzaman, SM; Rashid, AL; Chowdhury, A; Muazzam, N (Faridpur Medical College Journal, 2011)
This study was undertaken to find media better than routinely used media in isolation of uropathogens.Three hundred urine samples having pus cells >_ 5/ HPF were enrolled for the study. Comparison of isolation and identification of uropathogens among HiCrome UTI Agar media, 5% Sheep Blood agar & MacConkey agar and CLED agar media were done. Among them 95(31.67%) samples showed single growth, 6 (2%) showed mixed growth and 199 (66.67%) showed no growth. Rate of presumptive identification of organisms in primary culture plate were high in HiCrome UTI agar media. For Escherichia coli, it was 94.20% whereas in CLED agar it was 79.71% and by Blood agar and MacConkey agar media in combination it was 82.61%. All the Enterococcus spp. were identified in HiCrome UTI agar media, 33.33% in CLED agar media but none in Blood agar and MacConkey agar media. Among the mixed growth, 100% organisms were identified on HiCrome UTI Agar media due to distinct colour produced by the different organisms, whereas in one (16.67%) sample (mixed Esch.coli and Pseudomonas spp.) organisms were identified on other three media. Key words: UTI; Uropathogen; HiCrome UTI Agar media DOI: 10.3329/fmcj.v6i1.7411 Faridpur Med. Coll. J. 2011;6(1): 46-50